Diagnostic performance of human epididymis protein 4 compared to a combination of biophysical and biochemical markers to differentiate ovarian endometriosis from epithelial ovarian cancer in premenopausal women. Issue 12 (13th October 2017) - Nikolova, Tanja; Zivadinovic, Radomir; Evtimovska, Nina; Klisarovska, Violeta; Stanojevic, Marko; Georgievska, Jadranka; Nikolova, Natasha
Abstract: Aim: This study is a comparison of human epididymis protein 4 (HE4) with cancer antigen 125 (CA125), using the Risk of Ovarian Malignancy Algorithm (ROMA), Copenhagen Index (CPH‐I), Risk of Malignancy Index (RMI) and Morphology Index (MI) to differentiate ovarian endometriosis from epithelial ovarian cancer (EOC) in premenopausal women. Methods: The study was performed at the University Clinic of Obstetrics and Gynecology in Skopje. One hundred and sixty‐four premenopausal patients were divided into three study groups, including ovarian endometriosis (37), other benign pelvic masses (57) and EOCs (11), and a control group (59). After ultrasonography, all subjects underwent blood sampling. Surgery and histological verification was performed. Pelvic masses were classified based on histological findings. Mann–Whitney, receiver operating characteristic‐area under the curve (AUC), sensitivity, specificity and Kruskal–Wallis tests were used for statistical analysis. The level of significance α was set at 5%. Results: For each of the tested markers, sensitivity, specificity and accuracy to distinguish ovarian endometriosis from EOC were as follows: HE4 (81.82%, 100%, 95.83%); CA125 (81.82%, 48.65%, 56.25%); ROMA (90.91%, 83.78%, 85.42%); CPH‐I (81.82%, 97.30%, 93.75%); RMI (90.91%, 35.14%, 47.92%); and MI (100%, 75.68%, 81.25%), respectively. The AUC for ovarian endometriosis compared to EOC for tested markers was as follows: HE4 (AUC = 0.934), CA125 (AUC = 0.821), ROMA (AUC = 0.929), CPH‐I (AUC = 0.924) and RMI (AUC = 0.880), respectively. Conclusion: HE4 and CPH‐I perform best to discriminate ovarian endometriosis from EOC in premenopausal women. MI has maximal sensitivity to detect EOC.